THe THE PHENOMENON OF USING HARSH WORD IN ENGLISH AMONG INDONESIAN NETIZEN IN SOCIAL MEDIA - Imam_Mahdilawa Mahdilawa; Budi Santoso; M. Zahran Gibran; M. Imam Mahdilawa (Universitas Negeri Manado, 2023)
Abstract : Indonesian social media has developed rapidly over time. This is supported by an increasingly sophisticated Internet infrastructure, including WiFi access and fiber optic networks. Indonesians are becoming more and more active in the world of social media, reaching tens of millions of people. A social media presence certainly has both positive and negative effects, so any content can easily go viral. When interacting or communicating through these mediums, a great many people abuse the ethics of socializing in cyberspace by uploading or commenting using harsh language known as verbal abuse doing. According to Wardaugh idea (2010) There are 6 types of swear words, namely Excretion, Death, Body Function Term, Religious Matter, Mother in Law and Sex Term In (Suryadi et al., 2021). The purpose of this study is to determine the form of language used in social media and the form of comments on social media Facebook and Twitter posts. This research method uses a qualitative descriptive method. The source of the survey data comes from the social media Facebook and Twitter, but the data comes in the form of verbal abuse comments on Facebook and Twitter. Data collection techniques using documented techniques. Data analysis used qualitative analysis techniques and techniques to confirm the validity of the data performed by confirming the persistence of observations and member checks. We found that the form of speech used in Facebook and Twitter writing is straightforward, accurate, and clear. On the other hand, abusive comments on Facebook and Twitter posts include: Swearing, exaggeration, offense, stigma, and animal treatment. Words of verbal violence on Facebook and Twitter show that Indonesians are still not polite in their language, so information is needed for the government and educational institutions to take strategic steps to overcome this problem be the source. We found that the big amount of harsh words are 81 words of Sex term words which are “f*ck* or “what the f*ck” and the small amount of harsh words are 7 words of Personal background (conditions) which are “b*stard” and “g*y”.